2014
DOI: 10.1159/000365891
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Reduces Projection Neuronal Injury Induced by 3-Nitropropionic Acid in the Rat Striatum

Abstract: Background: Melatonin has shown a protective effect against various oxidative damages in the nervous system. Our previous studies have also confirmed its effect on behavioral dysfunction of experimental rats and injury of striatal interneurons induced by 3-nitropropionic acid. The present study aimed to further determine the effect of melatonin on the injury of striatal projection neurons induced by 3-nitropropionic acid. Methods: Classic histology, immunohistochemistry, Western blotting and immunoelectron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Also, HD is a destructive neurodegenerative disorder and indicates dysfunction in the neurons that may eventually lead to death of selected brain regions; especially, the striatum and cerebral cortex [ 5 ]. In recent studies, the dendritic spine density of striatal projection neurons was reported to be seriously decreased after 3-nitropropionic acid treatment [ 23 ]. This finding is in conformity with the results of the present study where dopamine levels increased in cortex, striatum and cerebellum/medulla oblongata regions of animals that received 3-nitropropionic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, HD is a destructive neurodegenerative disorder and indicates dysfunction in the neurons that may eventually lead to death of selected brain regions; especially, the striatum and cerebral cortex [ 5 ]. In recent studies, the dendritic spine density of striatal projection neurons was reported to be seriously decreased after 3-nitropropionic acid treatment [ 23 ]. This finding is in conformity with the results of the present study where dopamine levels increased in cortex, striatum and cerebellum/medulla oblongata regions of animals that received 3-nitropropionic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This protection applies to DNA, proteins, and lipids . There is certainly no shortage of studies that have unequivocally documented the ability of this molecule to attenuate the accumulation of free radical‐damaged molecules, for example, in ischemia–reperfusion injury , toxin exposure , inflammation , and many other clinically relevant situations . These benefits are apparent in both plants and animals .…”
Section: Melatonin Reduces Oxidative Stress: the Machinery And The Mementioning
confidence: 99%
“…The methods for Golgi staining were previously described in detail (26). At 4 weeks following the 6OHDA lesions, all the rats were deeply anesthetized with sodium pentobarbital (50 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%